Incidental radiological findings - Weckbach, Sabine (Springer, 2017)
Contents -- Contributors -- Part I: Introduction -- Incidental Findings: Definition of the Concept -- 1 Incidental Findings in a Broad Sense -- 2 Incidental Findings in a Narrow Sense -- 3 Incidental Finding or Signal Abnormality? -- 4 The Differing Indicative Dignity of Incidental Findings -- 5 The Context of the Occurrence of Incidental Findings -- References -- Incidental Findings - Ethical Aspects -- 1 Introduction -- 1.1 Frequency of Occurrence -- 1.2 Typical Fields of Ethical Challenges -- 1.3 Potential Outcome Resulting from the Question "Who Should Interpret the Images?" -- 1.4 Disclosure and Non-disclosure of IFs in the Research Context and Communication of Suspicious Findings in the Clinical Context -- 1.5 Positive and Negative Effects That May Arise from Decision About Which IFs Will Be Disclosed -- 1.6 The Approach to Disclosing IFs and Possible Consequences -- 2 Ethical Prerequisites and Principles -- 3 Recommendations -- 3.1 Disclosure Algorithms -- 3.2 Disclosure or Non-disclosure of IFs in the Research Context or the Communication of Suspicious Findings in the Clinical Context -- 3.3 Who Should Interpret the Images and Decide About the Disclosure of IFs? -- 3.4 Informing About the Handling of IFs/Consent Processes -- 3.5 Designing a Study Protocol in Research -- 4 Final Considerations -- References -- Medicolegal Aspects and Informed Consent -- 1 Frequency Engenders a Dilemma -- 2 Standard of Care -- 3 Defending an Ignored Incidentaloma in the American Courtroom -- 4 Medicolegal Duties of Researchers When Scanning Healthy Volunteers -- 5 Cascade of Unnecessary Imaging, Exposure to Radiation, and Informed Consent -- 6 Informed Consent -- 7 Conclusion: Incidentalomas and the Medicolegal Environment, 2016 -- 8 Author's Advice -- References -- Part II: IFs in Population Based Imaging/Research Setting
Keywords: Zufall; Befund; Radiologische Diagnostik